Thermal Activation of Thin Filaments in Striated Muscle - Ishii, Shuya; Oyama, Kotaro; Shintani, Seine A.; Kobirumaki-Shimozawa, Fuyu; Ishiwata, Shin’ichi; Fukuda, Norio (Frontiers in Physiology, 2020)
In skeletal and cardiac muscles, contraction is triggered by an increase in the intracellular Ca2+ concentration. During Ca2+ transients, Ca2+-binding to troponin C shifts the “on-off” equilibrium of the thin filament state toward the “on” sate, promoting actomyosin interaction. Likewise, recent studies have revealed that the thin filament state is under the influence of temperature; viz., an increase in temperature increases active force production. In this short review, we discuss the effects of temperature on the contractile performance of mammalian striated muscle at/around body temperature, focusing especially on the temperature-dependent shift of the “on-off” equilibrium of the thin filament state.